How to Spend It: Commodity and Non-Commodity Sovereign Wealth Funds - Reisen, Helmut (OECD Development Centre Policy Briefs, 2008)
Sovereign wealth funds have become important players in global financial markets. But their investments have repeatedly raised concerns, such as fear of industrial espionage or geopolitical threats. This paper argues that the principal motivation for setting up SWFs should put such concerns into the appropriate perspective. Development economics can explain both the funding sources and the motives that have led to the recent SWF boom, thus helping to prevent the imposition of investment restrictions in OECD countries